(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Premessa: fatti privati ed eventi storici di un decennio importante nella storia italiana - 2. Una tavola rotonda sul decennio 1958-1968 - 3. La disciplina costituzionale sui rapporti tra Stato e confessioni religiose. Un saggio recente sull’art. 7 della costituzione - 4. Nuova attenzione al tema dei rapporti tra Stato e Chiesa cattolica alla fine degli anni Cinquanta - 5. Il processo al Vescovo di Prato - 6. Il concilio Vaticano II e le trasformazioni della società italiana negli anni sessanta - 7. La morte di Togliatti. Le tendenze della giurisprudenza - 8. Il dibattito culturale e politico sulla riforma della legislazione ecclesiastica. 1958-1968: an important decade in the history of the relationship between “Stato e chiese” in Italy ABSTRACT: Individuals and experiences that, in the years between 1958 and 1968, had an important influence on the civic and political growth of the author. The experience of the participation in a conference on the historical period of the decade from 1958 to 1968. The constitutional provision on relations between the State and the Catholic Church in second post-war Italy, seen in the evaluation of a book published in 2017: critical considerations. New focus was given to the issue of relations between the State and the Catholic Church in the late fifties. The trial of the Bishop of Prato in 1958. The Second Vatican Council from 1962 to 1965 and the transformation of Italian society in the 1960s. The death of Togliatti on 21st August 1964 and the political consequences for Italy. Tendencies in the jurisprudence on the theme of relations between the state and religious confessions. The cultural and political debate on the reform of ecclesiastical legislation. After 1968, in Italy as in other countries, the phenomenon of extraneousness between the legal state and the real state is highlighted.